PELAYANAN ROOM BOY HOUSEKEEPING DEPARTMENT DI KTM RESORT - Siti Mariyam; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Batam is a city that has many tourist destinations and accommodations such as hotels and resorts, one of which is the 3-star KTM Resort, which is located at Colonel Soegiono, Tanjung Pinggir, 29432 Sekupang, Riau Islands, Indonesia. KTM Resort was established in 2002 and the name of the KTM resort was taken from the name of the owner of KTM namely